Correlation Between Neck Pain and Upper Limb Dysfunction in Non-Specific Neck Pain Patients - Dr Prachita Walankar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background & Aim Non-specific neck pain is defined as simple neck pain without any specific underlying disease that leads to pain. The aim of the present study was to find relation between neck pain and upper limb disability in nonspecific neck pain patients. Methodology Type of study is a cross-sectional study with purposive sampling method. 80 subjects in the age group of 18 – 40 years diagnosed with nonspecific neck pain were recruited. Subjects with cervical radiculopathy or existing upper limb pathology were excluded from the study. The Visual Analogue scale (VAS) was used to assess neck pain and Neck Disability Index (NDI) was used to measure the effect of neck pain on daily activities. The upper limb disability was measured using Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire. Results The results showed a significant positive correlation between VAS and DASH (r = 0.54, p= 0.000). Also, a significant positive correlation was found between NDI and DASH (r = 0.75, p= 0.000). Conclusion These findings provide evidence that there is relation between neck pain and upper limb dysfunction in non-specific neck pain disorders.